Pooled prevalence and associated factors of ECG abnormality among type 2 diabetic patients in the last ten years: Systematic review and meta-analysis - Mihret Getnet; Habtu Kifle Negash; Hailu Aragie; Hiwot Tezera Endale; Tseganesh Asefa; Winta Tesfaye; Yibeltal Yismaw Gela (PLoS ONE, 2025)
Background Type 2 diabetes mellitus is a global epidemic affecting millions of individuals worldwide. It is considered a chronic metabolic disorder of impaired glucose homeostasis, associated with various long-term complications and poor prognosis of cardiovascular performance. Therefore, this systematic review aimed to determine the pooled prevalence of ECG abnormality among type 2 diabetic patients both in the hospital setting and the general population based on the existing literature. Methods This systematic review has been conducted on the ECG abnormality of patients with Type 2 diabetes. Following the establishment of eligibility criteria, a literature search was conducted using three databases and two search engines. Included articles were then screened, critically appraised, and data extracted independently by two reviewers, and any disagreements were handled by the involvement of a third party. The quality of the included studies had been assessed using the New Castle Ottawa quality assessment scale tool. Pooled prevalence and sensitivity were determined by random effect analysis. Heterogeneity was assessed by Higgins’s I2, and its presence was alleviated by using sub-group analysis. Result Following the identification of 32, 785 studies, 33 publications were eligible for the review with a sample size of 31, 449. The pooled prevalence of ECG abnormality among Type 2 diabetic patients was 31% (95% CI: 25, 36%). It was 26% (95% CI: 1, 51%), and 31% (95% CI: 24, 37%) in the hospital and general/ community population, respectively. Body mass index (AOR =  5.90; 95%CI: 4.96, 7.03), duration of diabetic mellitus (AOR = 9.21; 95%CI: 9.12, 9.31), and being hypertensive (AOR = 5.17; 95%CI: 4.90, 5.46), were significantly associated factors with ECG abnormality among patients with Type 2 diabetic mellitus. Conclusion The pooled prevalence of ECG abnormality among Type 2 diabetic mellitus patients was high, while its magnitude was higher among patients attending hospital settings than in the community. Duration of diabetic mellitus, high body mass index and presence of hypertension were significant factors in this review. Moreover, we advise more longitudinal researches to determine the incidence of ECG abnormality among patients with diabetes considering time duration and sex differences. Ethical consideration Since our study was on the review of secondary data, ethical issues are not necessary